Silverlight 1.0 (Wiley Pub., 2008)
In these color-filled pages, a crack team of Wrox experts gives you a comprehensive introduction to Silverlight. You'll see the vivid graphics and video images you can achieve. You will learn to use the component languages, tools, and techniques of Silverlight to create applications that enhance the user experience. You'll also discover how to leverage existing technologies, such as JavaScript(r), XAML, ASP.NET, and AJAX, and incorporate them with development tools like Visual Studio(r), Expression(r) Encoder, and Expression Blend. Soon you'll be building everything from basic static pages to Internet applications that integrate rich media and animation.